Study on the optimal structure of nonmetallic coiled tubing with cable-laying based on the minimum stress in optical fibers - Houbu Li; Xueru Zhang; Xuemin Zhang; Nan Ding; Lei Li (Results in Engineering)
This study designs of three distinct nonmetallic coiled tubing structures, each featuring different configurations for the arrangement of optical fibers. The mechanical behavior of the cable integration layer, along with the optical fibers, is examined under internal pressure through finite element simulation analysis. The ideal configuration of the nonmetallic coiled tubing structure is determined with the objective of reducing the stress imposed on the optical fibers. The results indicate that the positioning of the cables significantly affects the stress experienced by each integrated layer of the pipeline. Conversely, this positioning exerts minimal influence on the stress distribution within the cables themself. The cables exhibit a distribution of alternating stress, characterized by regions of both high and low stress, across the three structures. The stress experienced by optical fibers under internal pressure is affected by their spatial arrangement and the compressive stress present in the fiber integration layer. The integration of optical fibers into the reinforcement layer leads to a reduction in stress on the fibers. In comparison to other configurations, this methodology yields a reduction in maximum stresses on temperature and vibration sensing optical fibers by approximately 9.4 % and 14.3 %, respectively. Furthermore, the maximum stresses on strain sensing optical fibers are diminished by 27.1 % and 17.0 %. Consequently, the design incorporating embedded optical fibers within the reinforcement layer represents the most optimal structure for cable installation. Utilizing this optimal structure, the corresponding nonmetallic coiled tubing with cable-laying is manufactured. Field tests indicate that the internal optical fiber has good monitoring ability.